Pengaruh Intervensi Aktivitas Fisik Berbasis Komunitas dalam Mengurangi Risiko Obesitas pada Remaja: Meta Analisis - Marjes N. Tumurang (Jurnal Sehat Mandiri, 2024)
Based on predictions in 2030, 38% of the world's adult population will be overweight and another 20% will be obese. Research objectives for community-based physical activity in reducing the risk of obesity in adolescents. Research Design is a meta-analysis that focuses on a comprehensive review of studies assessing the effectiveness of physical activity interventions in reducing the risk of obesity in adolescents aged 10-19 years published up to May 2024. Important aspects looked at are the type of intervention, participants, outcomes, study design . For the literature search, electronic scientific databases such as PubMed, Scopus, Web of Science, and Google Scholar were systematically explored. The search used the keywords "community-based physical activity interventions", "adolescents", "obesity", and variations of these terms. This meta-analysis included 8 studies. These findings demonstrated a statistically significant reduction in obesity risk associated with community-based physical activity interventions (pooled effect size = 0.75, 95% confidence interval 0.65–0.85). Subgroup analyzes showed varying impacts based on intervention type and duration, with significant differences in intervention effectiveness based on duration, with shorter interventions showing greater immediate effects, but longer interventions showing more sustained benefits over time. Conclusion :This meta-analysis underscores the importance of community-based physical activity interventions as an effective strategy to reduce the risk of obesity among adolescents